Anxiety, depression, and sleep disorders after COVID-19 infection - KOCAKAYA, DERYA (My University, 2023)
Introduction As of December 2019, the COVID-19 infection had spread rapidly across the globe, causing a pandemic. Although the virus primarily affects the respiratory and circulatory systems, neuropsychiatric disorders have been reported in a significant number of infected individuals. The aim of this study is to identify anxiety, depression, and sleep disturbances in the early post-COVID period, as well as potential risk factors. Method Symptomatic cases whose COVID-19 diagnosis was confirmed by polymerase chain reaction (PCR) positivity within the previous three months were evaluated in the COVID-19 follow-up clinic, where they were observed for at least four weeks after the diagnosis. Cases with no suspicious symptoms and no documented PCR positivity were selected as the control group. All participants completed the Hospital Anxiety Depression Scale (HADS) questionnaire and the Pittsburgh sleep quality questionnaire. The laboratory parameters of hospitalized patients with infection were recorded. Results A total of 283 patients were included in the study. While the median age of 144 patients with COVID-19 infection was 44 years, and 104 of them (72.2%) were female, the median age of the controls without COVID-19 infection was 52 years, and 65 of them (46.8%) were female. About 89 (61.8%) of the 144 patients with COVID-19 infections were hospitalized. When the results of the applied HADS questionnaire were analyzed, the median total value of all study participants was 10 points, whereas it was 13 in cases with COVID-19 and nine in those who did not have it (p<0.001). Taking into account the subgroups of the anxiety and depression questionnaires, both results are statistically significantly higher (p<0.001 and p=0.022, respectively) in post-COVID patients. When the hospitalization status of COVID-19 patients was compared, there was no difference in the development of anxiety (p=0.23), but depression (p<0.024) and poor sleep quality (p<0.001) were prevalent in hospitalized patients. The median PSQI score of the entire study population was five points, while it was seven points in cases with COVID-19 infection and four points in cases who did not have it (p<0.001). Sleep latency (p<0.003), sleep disturbances (p<0.001), and daytime dysfunction (p<0.001) were statistically significantly worse in COVID-19-infected patients. Female gender (p<0.01) and the presence of past anxiety-depression symptoms (p<0.013) were found to be as risk factors in patients with infection. The correlation between the total HADS score, the PSQI, and the results of the complete blood count and biochemical analysis at the time of diagnosis in hospitalized patients was also investigated. CRP (CI 0.26-0.58) p<0.001 vs (CI 0.09-0.45) p=0.004 and ferritin (CI 0.05-0.43) p=0.017 vs (CI 0.01-0.40) p=0.047 exhibited a positive correlation. Similarly, lymphocyte count (CI −0.65 to −0.37) p<0.001 vs (CI −0.39 to −0.01) p<0.001 and lymphocyte percentage (−0.57 to −0.24) p=0.001 vs (−0.65 to −0.37) p=0.039 were negatively correlated. Conclusion Early post-infection anxiety, depression, and sleep disturbances increased significantly in COVID-19 patients. Female gender and previous symptoms of anxiety and depression are risk factors, and inpatient treatment increases depression and poor sleep quality. High HADS and poor sleep quality scores are positively correlated with inflammatory parameters and should be evaluated in post-infection in particular.
Keywords: hospitalization in covid-19; covid anxiety; depression; sleep problems; covid-19